2016
DOI: 10.1159/000442830
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Normal Response during GH Stimulation Tests in Patients with Ectopic Posterior Pituitary Gland: A Source of False-Negative Diagnosis of Pituitary Insufficiency

Abstract: Aims: To report false-negative normal growth hormone (GH) peak response in patients with ectopic posterior pituitary gland (EPP) identified with a simplified magnetic resonance imaging (FAST1-MRI). Methods: We analyzed 75 EPP patients with short stature and reduced growth velocity. Sagittal-T1 imaging (thickness: 2 mm and gap: 0.2 mm) without gadolinium administration was used. A GH peak of ≥5 ng/ml after clonidine or insulin stimulation was considered normal. Results: Normal GH response was observed in 15 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…A recent study found that a GH response > 5ng/mL after insulin or clonidine stimulation is found in 20% of patients with EPP, so MRI imaging was proposed as a first line diagnostic approach of GH deficiency in these patients (41). Moreover, growth hormone deficiency may not be so evident in the first few years of life.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that a GH response > 5ng/mL after insulin or clonidine stimulation is found in 20% of patients with EPP, so MRI imaging was proposed as a first line diagnostic approach of GH deficiency in these patients (41). Moreover, growth hormone deficiency may not be so evident in the first few years of life.…”
Section: Discussionmentioning
confidence: 99%
“…Observou-se que, entre os pacientes com alterações na RNM que justificariam um hipopituitarismo, 24% não manifestavam deficiências hipofisárias.A progressão desses pacientes nas consultas seguintes não foi levantada, de forma a avaliar se em algum momento posterior esses pacientes evoluíram com deficiências hipofisárias, o que poderia alterar esta proporção. Um estudo retrospectivo conduzido porKochi et al (2016) avaliou 75 crianças referenciadas por BE e que apresentavam neurohipófise ectópica, e constatou-se que 20% dessas crianças apresentavam pico de GH estimulado normal em testes de clonidina e ITT (média de 8,2 ng/mL, ponte de corte considerado para DGH foi <5 ng/mL e a dosagem de GH sérico foi feita por IQMA)83 , o que reforça nosso achado e sugere que um resultado normal no teste de estímulo farmacológico de GH não necessariamente dispensa a realização de RNM.Por fim, em relação aos diagnósticos finais estabelecidos, observou-se que as causas englobadas pela BE isolada (BE familiar e/ou constitucional e BE idiopática), conforme proposto por Collett-Solberg et al2 , correspondem à maioria dos diagnósticos estabelecidos, somando uma proporção de aproximadamente 35%. Por sua vez, as condições associadas a alterações do eixo somatotrófico (DGH isolado e associado a múltiplas deficiências hipofisárias) correspondem a aproximadamente 26% da amostra.…”
unclassified